2008
DOI: 10.1211/ijpp.16.5.0007
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of criteria to identify medication-monitoring errors in care home residents

Abstract: Aim The identification of medication‐monitoring errors requires a validated definition. This paper describes the development and validation of a definition which includes criteria for specific medicines to determine whether a medication‐monitoring error has occurred in the care home setting. Setting Criteria were developed for older people (aged 65 years or older) living in care homes. Methods Criteria were developed by two clinical pharmacists using published guidelines. The criteria were divided into those r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Although the use of varying error definitions by researchers in determining error rates has been previously identified,[8,36,37,103] this review has confirmed that this problem still exists. This is reflected in the wide range (<1–>90%) of error rates reported.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although the use of varying error definitions by researchers in determining error rates has been previously identified,[8,36,37,103] this review has confirmed that this problem still exists. This is reflected in the wide range (<1–>90%) of error rates reported.…”
Section: Discussionmentioning
confidence: 64%
“…Monitoring -deviations from monitoring standards (Alldred et al [37] ); Dispensing -deviations from prescriptions and orders (Beso et al, 2005 [38] ); Administrationvariations between prescriptions and administrations (Dean and Barber, 2001 [39] ) Prescribing -8.3% (95% CI 7.1-9.5);…”
Section: Resultsmentioning
confidence: 99%
“…Five members of the research team then decided whether these fitted pre-specified definitions for prescribing and monitoring errors (Box 1). [10][11][12] A wide range of different types of errors were purposefully selected, including those that were considered particularly serious, a range of different types of potential prescribing and monitoring errors, potential errors involving problems at the primary-secondary care interface, and less serious problems, where GPs may have wished to debate whether or not an error had taken place. Letters were distributed to prescribers potentially responsible for these errors inviting them to participate in a face-to-face semi-structured interview.…”
Section: Resultsmentioning
confidence: 99%
“…The number of opportunities for error (denominator) was the number of prescription items written, plus any omissions. The three pharmacists worked to a common detailed protocol when reviewing the residents and their medicines, were trained together at the start of the study and had regular review meetings to ensure consistency. Monitoring errors were identified according to the definition developed and validated by Alldred et al 27 as “A monitoring error occurs when a prescribed medicine is not monitored in the way which would be considered acceptable in routine general practice. It includes the absence of tests being carried out at the frequency listed, with a tolerance of +50%.…”
mentioning
confidence: 99%